2020
DOI: 10.31234/osf.io/pbvya
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

If it’s important, then I’m curious: Increasing perceived usefulness stimulates curiosity

Abstract: Curiosity is considered essential for learning and sustained engagement, yet stimulating curiosity in educational contexts remains a challenge. Can people's curiosity about a topic be stimulated by evidence that the topic has potential value? In two experiments we show that increasing perceptions of value regarding a scientific topic also increases curiosity and subsequent information search. Our results also show that simply presenting interesting facts is not enough to influence curiosity, and that people ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In addition, these two studies investigated confidence separately from importance or utility (i.e., both as main effects) but did not investigate curiosity as a function of confidence and importance (i.e., both main effects plus the interaction between these two factors). Nevertheless, the results from Liquin and Lombrozo (2020), as well as Dubey et al (2019), provided further evidence showing that the perceived importance of information influences participants' curiosity.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…In addition, these two studies investigated confidence separately from importance or utility (i.e., both as main effects) but did not investigate curiosity as a function of confidence and importance (i.e., both main effects plus the interaction between these two factors). Nevertheless, the results from Liquin and Lombrozo (2020), as well as Dubey et al (2019), provided further evidence showing that the perceived importance of information influences participants' curiosity.…”
Section: Discussionmentioning
confidence: 78%
“…They also found that the effect of utility on curiosity was larger than the effect of confidence on curiosity. On a similar account, Dubey et al (2019) found that increasing the awareness of importance concerning a scientific topic also increased curiosity and that increased curiosity about a topic was followed by a higher willingness to learn about this information. Importantly, Liquin and Lombrozo (2020) as well as Dubey et al (2019) used a different paradigm as Kang et al (2009).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Religious and scientific knowledge are similar in many respects: Both involve culturally-transmitted worldviews containing socially-valued beliefs, causal models, values, and practices that determine what is real and true (Harris & Corriveau, 2014;Johnson et al, 2011). People are most curious when they perceive novel information as valuable (Dubey et al, 2019;, and given that religious individuals often express strong commitments to both scientific and religious traditions (e.g., Legare et al, 2012), curiosity may play an important role in learning about both topics. One key mechanism driving these effects could be the perception that curiosity signals willingness to exert effort to achieve socially desirable goals.…”
Section: Adults Show Positive Moral Evaluations Of Curiosity About Re...mentioning
confidence: 99%